Altruism, trust and reciprocity : an experimental analysis - Chai, Hui Yi (2011)
We conducted four studies: a Dictator Game, an Investment Game, and two hybrids of the two games. In the studies involving the Dictator Game, the recipient is a charity organization. All studies are double-blinded and non-repeated games involving real money. The purpose of the study is to observe the interactions between altruism, trust and reciprocity. We find that altruism and trust crowd out each other when in tension. When altruism and reciprocity are in tension, reciprocity are in tension, reciprocity is unaffected by altruism while altruism experiences a crowding out effect.